2012
DOI: 10.1186/1550-2783-9-24
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial leucine and insulin responses and toxicological effects of a novel whey protein hydrolysate-based supplement in rats

Abstract: The purpose of this study was: aim 1) compare insulin and leucine serum responses after feeding a novel hydrolyzed whey protein (WPH)-based supplement versus a whey protein isolate (WPI) in rats during the post-absorptive state, and aim 2) to perform a thorough toxicological analysis on rats that consume different doses of the novel WPH-based supplement over a 30-day period. In male Wistar rats (~250 g, n = 40), serum insulin and leucine concentrations were quantified up to 120 min after one human equivalent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In a study involving several animal models of insulin resistance, this peptide displayed antidiabetic effects, with a suppression in the elevation of blood glucose during an oral glucose tolerance test (36). In a recent study, Toedebusch et al (37) analyzed the postprandial effects of intact (WP) and hydrolyzed WPs (WPH) in Wistar rats. Higher serum Leu and insulin concentrations were observed after a 60-min gavage with WPH compared with WP.…”
Section: Discussionmentioning
confidence: 98%
“…In a study involving several animal models of insulin resistance, this peptide displayed antidiabetic effects, with a suppression in the elevation of blood glucose during an oral glucose tolerance test (36). In a recent study, Toedebusch et al (37) analyzed the postprandial effects of intact (WP) and hydrolyzed WPs (WPH) in Wistar rats. Higher serum Leu and insulin concentrations were observed after a 60-min gavage with WPH compared with WP.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, we speculate that the increase in Akt phosphorylation in the WPC and 70 W/30E groups may have been due to the superior ability of whey protein in stimulating insulin secretion and, thus, downstream insulin signaling in skeletal muscle. While we did not measure serum insulin responses in the current study, we have previously shown that WPH feeding to rats causes a robust (>2-fold) rise in insulin 60 min post-feeding [ 23 ]. Hence, foods containing a higher proportion of whey protein may stimulate greater intramuscular insulin signaling, and future research should continue to examine if WPC or WPH feeding in acute and long-term settings can enhance insulin sensitivity in insulin-resistant subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in vivo [ 19 , 20 ] and in vitro [ 21 ] evidence suggests that hydrolyzed whey or native whey protein increases the activation of postprandial intramuscular insulin signaling markers. Putative bioactive peptides from whey protein hydrolysates (WPH) have also been shown to exhibit insulin secretagogue properties versus intact whey protein [ 22 , 23 ]. Likewise, we have recently demonstrated that acute WPH feeding in rats increases the appearance of di- and oligopeptides as well as numerous lipolysis-related serum markers (i.e., epinephrine, glycerol and numerous free fatty acids) compared to an isonitrogenous WPC feeding condition [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other work on rodents found no evidence of renal damage; however, they did find that rats receiving a high protein diet experienced renal hypertrophy [2]. Notwithstanding, a more recent rat study reported that 30 days of very high whey protein supplemented diet (i.e., 6 human-equivalent 20 g doses per day) did not adversely affect blood and/or histological markers of liver or kidney health and instead may improve liver health when compared to rats not receiving protein [3]. …”
Section: Introductionmentioning
confidence: 99%